Omnichannel Marketing Strategies: Enhancing Customer Experience in the Digital Marketplace - Susbiyantoro, Susbiyantoro; Anggarini, Shinta Rahmani, Desy Tri (Pascasarjana STIE Amkop Makassar, 2025)
As digital technologies transform consumer behavior, businesses increasingly adopt omnichannel marketing strategies to meet rising expectations for seamless, personalized experiences. This qualitative study investigates how omnichannel strategies enhance customer experience by analyzing in-depth interviews with customers and marketing professionals across various industries. Thematic analysis revealed four core dimensions influencing experience quality: seamless channel integration, personalization through data synergy, perceived convenience and flexibility, and trust reinforcement via channel consistency. These findings suggest that successful omnichannel strategies depend not only on technological capabilities but also on organizational alignment, data integration, and customer empowerment. The study provides theoretical contributions to experiential marketing and offers practical guidance for businesses seeking to improve engagement and loyalty in the digital marketplace. Recommendations for future research include longitudinal and mixed-method approaches to examine evolving consumer expectations and industry-specific challenges. Keywords: Omnichannel Marketing, Customer Experience, Digital Marketplace, Channel Integration, Personalization, Qualitative Research